Investigations of solid liquid interfaces in ultra-thin liquid films via single particle tracking of silica particles - Trenkmann, Ines; Täuber, Daniela; Bauer, Michael; Schuster, Jörg; Bok, Sangho; Gangopadhyay, Shubhra; Borczyskowski, Christian von (Diffusion Fundamentals, 2009)
Single particle tracking with a wide field microscope is used to study the solid liquid interface between the viscous liquid tetrakis(2 ethylhexoxy)-silane and a silicon dioxide surface. Silicon dioxide nanoparticles (5 nm diameter) marked with the fluorescent dye rhodamine 6G are used as probes. The distributions of diffusion coefficients, obtained by mean squared displacements, reveal heterogeneities with at least two underlying diffusion components. Measurements on films with varying film thicknesses show that the slower component is independent of the film thickness, while the faster one increases with the film thickness. Additionally, we could show that the diffusion behavior of the particles cannot be sufficiently described by only two diffusion coefficients.